Shabanu daughter of the wind - Staples, Suzanne Fisher (New York DellLaurel-Leaf, 1989)
When eleven-year old Shabanu, the daughter of a nomad in the Cholistan Desert of present-day Pakistan, is pledged in marriage to an older man whose money will bring prestige to the family, she must either accept the decision, as is the custom, or risk the consequences of defying her father's wishes.
Sequel: Haveli.
Keywords: Cholistan Desert (Pakistan) -- Fiction; Pakistan -- Fiction; Sex role -- Fiction